Assessing Inclusivity of Faculties and School at Sebelas Maret University Utilizing UNS Inclusion Metric Standards - Munawir Yusuf; Joko Yuwono; Ummul Mustaqimah; Mahardika Supratiwi; Leni Ambar Cahyani (FKIP Universitas Lampung, 2024)
Assessing Inclusivity of Faculties and School at Sebelas Maret University Utilizing UNS Inclusion Metric Standards. Objectives: There are many problems in implementing inclusive education in higher education. Therefore, it was needed to conduct a research that discusses the level of inclusivity comprehensively starting from attitudes, policies, to implementation in higher education. Methods: This research aimed to determine the level of inclusivity of 15 faculties at UNS through a survey of lecturers, education staff and students. The instrument used was the UNS Inclusion Metric which consists of an attitude assessment and a self-evaluation report form (LED). Data analysis was carried out by calculating the total score, average and standard deviation (SD). Findings: The research results showed that FKIP, FMIPA, and FISIP exhibit high inclusivity scores, indicating a strong commitment to inclusivity. FEB, FH, FIB, FSRD, FIK, FK, FPsi, and FPet were in the moderate inclusivity category. Meanwhile, FATISDA, FT, and FP showed low inclusivity scores, indicating significant challenges in achieving full inclusivity. Conclusion: These findings highlight the importance of inclusive training for lecturers and staff and the need to overcome physical barriers to achieve an inclusive educational environment. Keywords: inclusivity, UNS inclusion metric, higher education.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202480